Hygiene; Sebuah Budaya yang Terbuang namun Dirindukan - Muhamad Misbahudin; Agus Setiawan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
This paper aims to explain and explore the understanding of the Islamic boarding school community about cleanliness. This historical, anthropological research uses an ethnographic method with a postcolonial approach. The focus is on community activities in Ponorogo in applying their understanding of cleanliness. The argument of this paper is that the efforts of the people of Ponorogo in implementing cleaning activities are more of a strategy for maintaining a